ntracellular Localization of HBV Capsid in Hepatocyte Line After Transfected by The Entire HBV Genome = Lokalisasi Intraseluler Kapsid HBV Pada Sel Line Hepatosit Setelah Ditransfeksi Dengan Genom Utuh HBV. - Aris Haryanto; Michael Kann (Jurnal Sain Veteriner, 2006)
HBV replicates within the nucleus of hepatocyte using cellular transport machinery for the import of their genomes into the nucleus. Genome of HBV has to transported through the cytoplasm towards the nuclear pore complex (NPC) followed by subsequent passage through the pore. HBV capsid is involved in a number of important functions in the replication cycle of HBV. It can be detected in the nucleus, cytoplasm or both within infected hepatocytes. Nuclear localization of HBV capsid protein, which is karyophilic, depends on the cell cycle. The objective of the present study was to analyzes the intracellular localization of HBV capsid protein after transfected by entire HBV genome into hepatocyte cell lines (HuH-7) and to determine the predominantly localization of the capsid into cell compartment. In this work we analysed the intracellular localization of the HBV capsid in human hepatocyte cell lines liuH-7 by transfection using entire HBV genome and transient expression. The transfected cells were fixed and an indirect immune staining against the HBV capsid was performed to detect the capsid. To verify the location within the cell, an additional co-staining against the nuclear pore complexes was performed. The Intracellular localization of the HBV capsid and NPC were analyzed by a confocal laser scan microscope. The observed of localizations into the transfected cells were classified to be predominantly as nuclear localization, cytoplasmic localization or distributed within both of these compartments. Result of this study indicated that Staining of HBV capsid found predominantly within the nucleus (71%). Less frequently, the HBV capsid localized within the cytoplasm (26%). Only in a minority of cases, the capsids were localized within cytoplasm and nucleus (3%). This low frequency indicate that the capsids were not diffusing within the cells being in accordance to the in vivo situation in which the nuclear membrane was impermeable for the capsid.